De Ben Jelloun à Mouftakir : dialogues intertextuels entre littérature et cinéma - Karima Benelbida (Carnets)
Just like L’enfant de sable by Tahar Ben Jelloun, Pégase is steeped in legend, references, and, more fundamentally, ancestral storytelling. Through this 2010 film by Mohamed Mouftakir, we will explore the concept of intertextuality by analyzing the borrowings and interrelations between the two works, both cinematic and literary.In studying this relationship between the two productions, we will focus on the rhythm of the narrative, the question of erasure/displacement, and the intertextuality between mystery and folktale. This article will also attempt to discuss otherness/identity, looking at both convergence and divergence, as well as mysticism surrounding sacredness and the notion of gender.